Investigation of REBCO Roebel Cable Irreversible Critical Current Degradation Under Transverse Pressure - Murtomaki, Jaakko Samuel; Kouhia, Reijo; Stenvall, Antti; Bottura, Luca; Kirby, Glyn; van Nugteren, Jeroen; de Rijk, Gijs; Rossi, Lucio (IEEE transactions on applied superconductivity, 2018)
The Roebel cable utilized in High Field accelerator magnets is subject to high transversal electromagnetic forces. The conductor response to exerted pressure depends from the geometry and materials of the cable. A transverse loading test was performed for an impregnated cable in cryogenic conditions. The test revealed Roebel cable being able to withstand elevated average pressure level common to dipole magnets, when the pressure load is exerted by a stiff press tool. However, the mechanism for irreversible current degradation during the transverse loading during powering remains so far unknown. This paper focuses on finding likely failure mechanisms when a magnet is powered. The cable is wound with a glass-fiber sleeve and impregnated with epoxy. Epoxy has much lower stiffness than the coated conductor. When the cable is subjected to transverse loading, abrupt changes in cable thickness and material properties may lead to irreversible degradation of the conductor. As the tape crosses the epoxy-filled central gap region of the cable, the discontinuous change of the support stiffness generates bending strains and shear stress in the conductor. The cable is mechanically modeled. By modeling, the measured axial strain limit of the conductor is connected to transverse pressure limit of the cable.